2015
DOI: 10.1021/acs.nanolett.5b00199
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time in Situ Probing of High-Temperature Quantum Dots Solution Synthesis

Abstract: Understanding the formation mechanism of colloidal nanocrystals is of paramount importance in order to design new nanostructures and synthesize them in a predictive fashion. However, reliable data on the pathways leading from molecular precursors to nanocrystals are not available yet. We used synchrotron-based time-resolved in situ small and wide-angle X-ray scattering to experimentally monitor the formation of CdSe quantum dots synthesized in solution through the heating up of precursors in octadecene at 240 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 42 publications
3
110
0
2
Order By: Relevance
“…The method was also used to study the growth mechanism of the CdSe NPs. 103 From the NP size distribution and NP concentration data obtained, the growth of the NPs was thought to be limited by the thermal activation of the Se precursor. Using the in situ X-ray scattering, the fast nucleation and growth kinetics of Ag NPs were studied.…”
Section: Formation Of Monodisperse Nanoparticlesmentioning
confidence: 99%
“…The method was also used to study the growth mechanism of the CdSe NPs. 103 From the NP size distribution and NP concentration data obtained, the growth of the NPs was thought to be limited by the thermal activation of the Se precursor. Using the in situ X-ray scattering, the fast nucleation and growth kinetics of Ag NPs were studied.…”
Section: Formation Of Monodisperse Nanoparticlesmentioning
confidence: 99%
“…As only one superimposed scattering curve is recorded, data interpretation is challenging and cross-validation against other, independent techniques is required. However, once established for a certain system, SAXS is a powerful technique for particle analysis (Abécassis B. et al, 2015;Caetano B.L. et al, 2010;Polte J. et al, 2010).…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%
“…These time‐dependent parameters of CNPs are then used to fit Equation (4) or Equation (5) to determine the growth mechanism of the CNPs. These parameters can also be obtained from the Monte‐Carlo fitting of the SAXS patterns using Equation (8), where all the parameters are randomly chosen with little or no empirical knowledge . For example, Wu et al used in situ SAXS to study the synthesis of monodisperse Pd CNPs in octadecene containing Pd(acac) 2 (acac=acetylacetonate) as precursor reactant and various amounts of trioctylphosphine(TOP), oleic acid, and oleylamine as surfactant ligand .…”
Section: Early Growth Stage (Stage Ii)mentioning
confidence: 99%
“…This strategy can also be used to study the synthesis of monodisperse CNPs in the presence of a micelle phase. For example, Abécassis et al observed the melting of lamellar micelles and the following formation of small micelles (<1 nm) in the synthesis of CdSe NPs using the combined in situ SAXS and WAXS . Yi et al used in situ SAXS to reveal the role of tetraethylorthosilicate/cetyltrimethylammonium bromide (TEOS/CTAB) micelles in the synthesis of mesoporous silica NPs …”
Section: Early Growth Stage (Stage Ii)mentioning
confidence: 99%